Pedagogical Content Knowledge (PCK) of Islamic Education Teachers in Improving the Quality of Islamic Education Learning - Eva Dwi Kumala Sari; Yustina .; Wathroh Mursyidi (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2020)
Life in the era of revolution 4.0, students are expected to have qualified religious training in school education, so that they are always ready for the rapid changes of the times without reducing their faith and piety as a Muslim. This of course must be supported by the pedagogical ability of Islamic Education teacher content knowledge, where with good mastery of Islamic Education knowledge, will love the religious climate among students, and can produce quality Islamic Education learning in schools. The purpose of this study was to determine the effect of Islamic Education Teacher Pedagogical Content Knowledge on the Quality of Islamic Education Learning in schools in Bekasi City. This research was conducted at MGMP Bekasi City and Bekasi Junior High School students. The sample in this study were 30 teachers and 30 junior high school students using simple random sampling. The data in this study were analyzed using simple regression analysis, with a significance level of α = 0.05, to determine the significance of the X and Y correlation coefficients at a = 0.05. The validity of the data used the prerequisite test with the normality test and the linearity test. The results of the study concluded that there was a relationship between pedagogical content knowledge and the quality of Islamic education learning as indicated by a thit of 1.403 and p-value = 0.000 <0.05, so H0 was rejected. Thus, pedagogical content knowledge has a positive effect on the quality of Islamic education learning in schools in Bekasi City. Judging from the table summary model R Square which is worth 0.793, so pedagogical content knowledge affects the quality of Islamic education learning outcomes by 79.3%.